Negative Pressure Wound Therapy in the Head and Neck: An Evidence‐Based Approach. (22nd August 2018) - Mir, Ahsan; Guys, Nicholas; Arianpour, Khashayar; Svider, Peter F.; Rayess, Hani; Zuliani, Giancarlo; Raza, S. Naweed; Lin, Hosheng
Abstract : Objective: To perform an evidence‐based review with recommendations that evaluates the indications and utility of negative pressure wound therapy (NPWT) in the head and neck. Methods: The authors searched the PubMed, Medline, Embase, Web of Science, and Cochrane Library databases for relevant literature. The primary outcome was successful intended use of NPWT, be it for granulation tissue formation, infection control, or complete wound closure. Patient demographics, etiology, and other clinical characteristics were explored. Meta‐analysis of observational studies was used to examine response rates and wound sizes. Results: Fifty‐seven articles encompassing 522 patients were included. The most common etiologies reported included: neoplasm (343 patients [65.7%]), oro‐/pharyngocutaneous fistula (9.8%), infection (10.5%), and trauma (9.6%). The majority of wounds treated were in the neck (61.6%). Potential risk factors that may compromise wound healing were noted in 217 of 522 patients (41.6%). Of these 217 patients, 135 had properly documented risk factors, with the most common being prior irradiation (63%). The overall mean response across studies was 85.7% (95% confidence interval: 0.806–0.896, P  < 0.001, I 2  = 0 %). Conclusion: Negative pressure wound therapy is useful for the management of head and neck wounds and should be considered for patients in whom wound healing is progressing insufficiently, including those with a history of head and neck cancer, oro‐/pharyngocutaenous fistula, and trauma. Randomized controlled trials further comparing NPWT versus other modalities may be invaluable in further delineating its appropriate role. Laryngoscope, 129:671–683, 2019